2017
DOI: 10.1111/imig.12382
|View full text |Cite
|
Sign up to set email alerts
|

Peaceful Returns: Reversing Ethnic Cleansing after the Bosnian War

Abstract: This article focuses on post-Dayton Bosnia and Herzegovina to investigate decisions of forced migrants to return home to their pre-conflict residences. We formulate a set of novel hypotheses on the demographic determinants of return as well as on the role of social capital, national ideology, integration, and war victimization. We use a 2013 Bosnian representative sample with 1,007 respondents to test our hypotheses. The findings support the expectation that gender and age have a major impact on return. Net of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…These tendencies could be aggravated if the right of return is either restricted or difficult to implement after the passage of time, as in Cyprus. Thus far, the evidence on return in post-conflict communities is mixed, with some finding it feasible under specific conditions (Stefanovic and Loizides, 2017) and others, unrealistic (Adelman and Barkan, 2011; Zolberg et al, 1986). Even though the literature identifies the pitfalls of securitizing displacement crises and their victims (Greenhill, 2010; Jacobsen, 2002), few public opinion studies challenge these claims or point to potential pro-peace attitudes among IDPs.…”
Section: Intergroup Relations and Internally Displaced Personsmentioning
confidence: 99%
“…These tendencies could be aggravated if the right of return is either restricted or difficult to implement after the passage of time, as in Cyprus. Thus far, the evidence on return in post-conflict communities is mixed, with some finding it feasible under specific conditions (Stefanovic and Loizides, 2017) and others, unrealistic (Adelman and Barkan, 2011; Zolberg et al, 1986). Even though the literature identifies the pitfalls of securitizing displacement crises and their victims (Greenhill, 2010; Jacobsen, 2002), few public opinion studies challenge these claims or point to potential pro-peace attitudes among IDPs.…”
Section: Intergroup Relations and Internally Displaced Personsmentioning
confidence: 99%
“…The number of officially registered returnees by the UNHCR greatly differed from reality, and, due to that, they were disputed. Researchers who focused on minority return in BiH concluded that the number of real returnees is much lower than the UNHCR data suggests (Čermák 2018;Stefanovic & Loizides 2017;Žíla 2014;Jansen 2011;Haider 2009). The UNHCR statistics registered the current situation on the ground.…”
Section: The Successful Minority Return and Limitations Of Its Measurmentioning
confidence: 99%
“…Although little is known on return migration after conflict (Joireman, 2017), several hypotheses try to explain the reasons why some people return but not others; including war trauma, political pressure, integration, gender and age-related factors, social capital and security hypotheses (Stefanovic and Loizides, 2017).…”
Section: Main Reasons To Return or To Stay In Displacementmentioning
confidence: 99%
“…"While household characteristics, economic situation, length of displacement and experiences prior to leaving are all important in the decision of a household to return, the most important issue is security" (Joireman, 2017). The presence of members with a different ethnic, religious or tribal background in the location, civilians or military forces, is a spur to fear of violence which influence the decision not to return (Stefanovic et al, 2014); in particular when the displaced group is minorityunderstood as the group with less power in a situation of post-conflict-in origin (Stefanovic and Loizides, 2017). Analysis of the main reasons -first and second reason combinedgiven by returned IDPs on why they returned and by IDPs on why they were staying in displacement (Table 5), showed security as a strong determinant among both groups.…”
Section: Main Reasons To Return or To Stay In Displacementmentioning
confidence: 99%